The effectiveness of applying mathemagic as an alternative method of Joyful learning for junior high school students - Qoyyimah, Annisaul; Maswar, Maswar (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
This study aims to analyze the effectiveness of the mathemagic method as one of the alternatives to joyful learning methods for junior high school students. The objects of this study were students of State Junior High School 1 Situbondo, consisting of 30 students in the experimental class and 30 students in the control class. Data were collected through test instruments and questionnaires, then analyzed using descriptive and inferential statistics in the form of paired sample t-tests, and N-Gain tests. The results of the study showed that the application of the mathemagic method as an alternative joyful learning is effective in improving student learning outcomes on HOTS questions, with an average increase in scores from pre-test (68.80) to post-test (87.83) of 19.03 points in the experimental class compared to pre-test (63.23) to post-test (73.20) of 9.97 points in the control class, sig.t (p-value) 0.000 < 0.05. The N-Gain analysis was 61.71% (moderate category) in the experimental class, while the control class was 27.24% (low category). In addition, 85% of students gave a positive response to this method, especially in terms of motivation and interest in learning because it was considered interesting and enjoyable.